#TITLE_ALTERNATIVE# - HARIS (NIM : 35005009); Tim Pembimbing : Prof. Ir. Amrinsyah Nasution, MSCE, Ph.D; Dr. Ir. Si, ABDUL
This paper is provoked by measurement result from vibration-monitoring of a number of offshore structures. This measurement is carried out in order to get natural frequencies as an indicator of structural integrity of an offshore structure. There are significant difference between natural frequencies from measurement and computer simulation model. It is caused by the fact that hidrodynamic damping effect is simplified by applying additional mass. Since computational technology grows very rapidly, fluidstructure interaction can be accomodated without enormous computational effort. In this study, fluid-structure interaction is included into simulation model by applying smart itterative algorithm without any simplification such as linearization. Analysis model was validated to measurement results of natural frequencies of actual structures on site.This new approach has shown more rational result if it is compared to conventional model. After getting more rational simulation model without any degradation, this study is extended to develop dynamic simulation of long term-degradation of fixed-jacket structure. Long term-degradation considered in this study come from corrosion process by applying artificial degradation scenarios. Subsidence,marine growth and soil-structure are not considered in this study. A large number of dynamic behaviour of various extracted dynamic analysis is carried out. Natural frequencies of modified analysis model which is incorporated fluid-structure interaction approaches measurement result until 85%. Then, analysis model is developed in order to simulate dynamic structural behaviour by introducing extracted dynamic analysis of ageing offshore structure. Simulation result has shown that hidrodynamic damping is significant where in this case study reducing response until 40%.